2018
DOI: 10.1016/j.celrep.2018.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Aminobutyric Acid Signaling in Brown Adipose Tissue Promotes Systemic Metabolic Derangement in Obesity

Abstract: Brown adipose tissue (BAT) is a metabolically active organ that contributes to the maintenance of systemic metabolism. The sympathetic nervous system plays important roles in the homeostasis of BAT and promotes its browning and activation. However, the role of other neurotransmitters in BAT homeostasis remains largely unknown. Our metabolomic analyses reveal that gamma-aminobutyric acid (GABA) levels are increased in the interscapular BAT of mice with dietary obesity. We also found a significant increase in GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…It has been recently reported that GABA might be involved in the regulation of obesity and energy metabolism (43,(53)(54)(55). In pro-opiomelanocortin neurons, GABA B receptor ablation results in increased obesity and insulin resistance via dysregulation of the appetite (53).…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently reported that GABA might be involved in the regulation of obesity and energy metabolism (43,(53)(54)(55). In pro-opiomelanocortin neurons, GABA B receptor ablation results in increased obesity and insulin resistance via dysregulation of the appetite (53).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in experimental animals, high fat diet leads to a chronic up-regulation of the GABA-BR1 in adipose tissue and its translocation into cellular membrane, making adipocytes of obese animals more sensitive to the damaging effects of GABA. In turn, suppression of excessive signaling by the inhibition of mitochondrial calcium overload restores normal BAT function [ 40 ].…”
Section: Adipose Tissue Browningmentioning
confidence: 99%
“…More recently, it has been shown that HFD increases UCP1 thermogenic protein in mice and rats [115,116] and BAT temperature after 20 weeks of diet [117]. Importantly, it has been demonstrated that the levels of gamma-aminobutyric acid (GABA), an inhibitory neurotransmitter that suppresses neuron excitability, are increased in BAT of HFD-fed mice promoting BAT disfunction [118]. All these exiting results provide new insights into innervation patterns and nerve plasticity in adipose depots, suggesting that neuromodulation could become an essential strategy to explore new ways to treat obesity (reviewed in [119][120][121][122]).…”
Section: Physiological Mechanisms Involved In Diet-induced Obesitymentioning
confidence: 99%